Kerusakan Tulang Alveolar Tipe Horisontal Pada Wanita Muda Dengan Penyakit Periodontal Disertai Diabetes Melitus Tipe-1 Tidak Terkontrol (Laporan Kasus) - Wibowo, Frediyuana Dhameswara; Utami, Nuryanni Dihin (Mulawarman Dental Journal, 2022)
Background: Periodontitis is an inflammatory disease that occurs in periodontal tissue. Etiology of chronic periodontitis was local factor due to toxin from bacteria in plaque and calculus accumulation and systemic factors as diabetes melitus. Diabetes melitus was a metabolic disease in which blood sugar levels are abnormally because the body does not regulation enough insulin absolutely  (type-1) and insulin deficiency (type-2). Aim:this case report was to explain the condition of chronic periodontitis and management that occurs in patients with diabetes melitus. A 23-year-old woman to have a type-1 diabetes melitus uncontrol complained that her gingiva redness and bleded easily for about two month ago. Case discussion: Intraoral examination shows gingival oedem in each region, gingival recessions in the anterior maxilla and anterior posterior mandible, mobility teeth 35 degree 1 because periapical abscess, loss of teeth 18, 36, 37, 46 and 47. Conclusion: Patients were instructed to education, control plaque and calculus with scalling and root planning, re-treatment root canal 35 teeth and making of removable partial denture. Patients with diabetes melitus have decreased immune response and cell function, this condition can inhibit the process of tissue repair, to increase the severity of periodontal disease.Keywords: Chronic Periodontitis, Plaque, Calculus, Diabetes Melitus, Periodontal Tissue